Evaluación del efecto de tres concentraciones de CO2 en el cultivo de remolacha (Beta vulgaris) bajo invernadero en el sector Salache, Cantón Latacunga, Provincia de Cotopaxi 2022. - Jiménez Jiménez, Klinger Rodolfo (2022)
The purpose of this research study was to evaluate the effect of three CO2 concentrations on the beet (Beta vulgaris) crop at the Technical University of Cotopaxi, in the Salache sector at an altitude of 2800 meters above sea level, it was carried out under greenhouse conditions with 450 ppm minimum CO2 located in Andean grains. A carbon dioxide generator was used to increase the concentration levels and inject it into the beet crop (Beta vulgaris). Three concentrations of CO2 (650 ppm, 850 ppm, 1000 ppm) were applied at two exposure times (time 1, four hours, time 2, six hours) with a randomized complete block experimental design in AxB+1 factorial arrangement with 3 replications. When evaluating the effect produced by CO2 on the beet crop (Beta vulgaris). The stable dose of CO2 application in plant height was C3T1, (1000 ppm CO2, 4 hours of exposure), with 24.75 cm high, in the length and width of the leaf predominates C2T2 (850 ppm CO2, 6 hours of exposure), with 13.79 cm long and 8.20 cm wide, the appropriate dose for the number of leaves was C1T1 (650 ppm CO2, 4 hours of exposure), with a percentage of 8 leaves, in the C1T1 run (650 ppm CO2, 4 hours of exposure), with 35.17 mm tuber diameter, 0.11 kg tuber weight with leaves and 0.047 kg tuber weight without leaves, the best CO2 dose for chlorophyll was C2T2 (850 ppm CO2, 6 hours of exposure), with a percentage of 15.79%. Therefore, it is recommended to use concentrations of 650 ppm and 850 ppm of CO2 under greenhouse conditions to improve the photosynthetic process of the plant.